2016
DOI: 10.5327/z2176-947820160051
|View full text |Cite
|
Sign up to set email alerts
|

Acumulação de microcistinas no mexilhão dourado Limnoperna fortunei e riscos para a biota aquática

Abstract: Endereço para correspondência:Alessandro Minillo -Universidade Estadual do Mato Grosso do SulRodovia Dourados/Ithaum, km 12, 7804-9970 -Dourados (MS), Brasil -E-mail: alminillo@yahoo.com.br RESUMOAs cianobactérias representam um componente natural da comunidade fitoplanctônica, mas estão frequentemente associadas com águas eutrofizadas. Os rios do estado de São Paulo estão em processo contínuo de eutrofização, o que favorece frequentes florações de cianobactérias, prejuízos à qualidade da água para o consumo h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…In spiked treated municipal wastewater, Mezzanotte et al ( 2016 ) found a significant reduction in rotavirus that can cause gastroenteritis, and although the viruses remained in the soft zebra mussel tissues or in the liquid phase, they were not transmissible to other species. The ability to bioaccumulate microcystins by zebra and golden mussels can potentially be used for biomonitoring of toxic cyanobacteria blooms (Paldavičienė et al, 2015 ; Minillo et al, 2016 ).…”
Section: Regulating and Supporting/maintenancementioning
confidence: 99%
“…In spiked treated municipal wastewater, Mezzanotte et al ( 2016 ) found a significant reduction in rotavirus that can cause gastroenteritis, and although the viruses remained in the soft zebra mussel tissues or in the liquid phase, they were not transmissible to other species. The ability to bioaccumulate microcystins by zebra and golden mussels can potentially be used for biomonitoring of toxic cyanobacteria blooms (Paldavičienė et al, 2015 ; Minillo et al, 2016 ).…”
Section: Regulating and Supporting/maintenancementioning
confidence: 99%
“…Nessa linha, sublinhamos que algumas florações de algas, especialmente cianobactérias, frequentemente associadas com águas eutrofizadas (MINILLO et al, 2016), são tóxicas para plantas e animais. Essa toxidade pode levar ao decréscimo da biodiversidade e representar um risco para a saúde humana por liberar compostos orgânicos que geram sabor e odor e que, em alguns casos, podem ser precursores de trialometanos (THM) (SALAMEH;HARAHSHEH, 2011).…”
Section: Introductionunclassified